A renewable lignin-derived bio-oil for boosting the oxidation stability of biodiesel. (January 2022) - Umar, Yusuf; Velasco, Orlando; Abdelaziz, Omar Y.; Aboelazayem, Omar; Gadalla, Mamdouh A.; Hulteberg, Christian P.; Saha, Basudeb
Abstract: The valorisation of lignin is being increasingly recognised to improve the economics of pulp and paper making mills. In the present study, an integrated lignin–glycerol valorisation strategy is introduced with an overarching aim for enhancing the process value chains. LignoBoost kraft lignin was subjected to base-catalysed depolymerisation using glycerol as a co-solvent. The generated bio-oil was used as a renewable additive to biodiesel for enhancing its oxygen stability. The influence of three independent parameters including temperature, time and glycerol amount on lignin depolymerisation was investigated. Response surface methodology was applied to design the experiments and to optimise the process for maximising the yield and antioxidant impact of bio-oil. The results showed that glycerol has a positive qualitative and quantitative impact on the produced bio-oil, where an enhancement in the yield (up to 23.8%) and antioxidant activity (up to 99 min induction period) were achieved using the PetroOxy method (EN16091). The addition of 1 wt% bio-oil to biodiesel has led to an improvement in the oxidation stability over a neat sample of up to ∼340%, making it compliant with European standard (EN14214). The proposed process presents a biorefinery paradigm for the integrated utilisation of waste cooking oil, lignin and glycerol. Graphical abstract: Image 1 Highlights: Bio-additives from the base-catalysed depolymerisation of LignoBoost kraft lignin. Effect of reaction variables on bio-oil yield and biodiesel oxidation stability. Oxidation stability of biodiesel increased up to 340% by adding 1 wt% bio-additive. An integrated biorefinery concept for valorising lignin and glycerol waste streams.